Literary projection of the disintegration of Yugoslavia - Andrejević, Danica (Napredak, 2021)
The research of the poetic and cultural meaning of literature from the 1990s to the present moment can, in the culturological context, be conducted within the social, historical and anthropological sphere as well as the general culture of remembrance. The literary projection of the dissolution of Yugoslavia in this case spans the last three decades of development of Serbian literature. In this paper we apply an interdisciplinary approach to interpretation, in accordance with the author’s aspects. The basic theoretical framework consists of points of view of various characters who in monologues or within other narrative forms of literary discourse, articulate their position on the tragic the ruptures within the state, family, being. Selected prose statements are structural-poetic and semantic-axiological messages of different authors and characters. About twenty novels of all generations of authors are included, which are more or less explore the topic of the last civil war in the Balkans. The model of citation characteristic of the theme is contrasted by the varying subjective attitudes of the characters, ideologically colored or politically correct. Excerpts were selected exclusively on the basis of their literary value. Writers react more intensely, freely, and emotionally to the tragic reality and war apocalypse.